EDUKASI DAMPAK BAHAN KIMIA BERBAHAYA PADA PRODUK KOSMETIK DI SMK KESEHATAN DI KOTA BANDAR LAMPUNG - Ariawan, M. Wahyu; Wigatiningtyas, Ariska; Muh. Deni Kurniawan; Abidssalam, Erfan; Ramadhani, Dalifa (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This community service program aims to educate students about the dangers of chemicals in cosmetic products and instill discipline in learning among students at Bandar Lampung Health Vocational School. The use of cosmetics containing hazardous materials such as mercury and hydroquinone is a crucial health issue among adolescents, while discipline in learning is an important foundation in understanding health literacy. Activities are carried out through counseling methods, interactive discussions, and simulations of effective learning strategies (experiential learning). Materials include identifying safe cosmetics, detecting hazardous chemicals, and the application of time management and time blocking in learning. The results of the activity showed a significant increase in students' understanding of cosmetic safety, accompanied by positive changes in disciplined learning behavior. Students were able to practice how to choose safe products and create independent study schedules. The synergy between health materials and the development of disciplined character has proven effective in building awareness, intrinsic motivation, and academic responsibility in students.